Determination of torque for milling working equipment of excavator when repairing a pipeline - I. S. Kuznetsov (Вестник СибАДИ, 2023)
Introduction. During the overhaul of the pipeline to remove the soil under the pipe, a trench tool is currently used. The new technology of excavation of soil under the pipeline proposed by the authors, which provides for the use of replaceable milling working equipment for a hydraulic excavator, makes it possible to increase the speed of repair work. The purpose of the article is a theoretical study of the process of interaction between the structural elements of milling equipment and the developed soil.Methods and materials. Based on the basic provisions of the theory of interaction of the working bodies of earthmoving machines with the soil, a mathematical model of the work of the milling working equipment of a hydraulic excavator was created. It makes possible to get the dependence of the resistance forces arising on the cutters of the working equipment, on its design parameters and the physical and mechanical properties of the soil.Results. According to the results of the analysis of the obtained dependence of the torque on the cutting angle and the angular speed of rotation of the milling head, it was found that the greatest influence on the torque required to overcome the forces of soil resistance and the drive of the working body is exerted by the angular speed of rotation of the milling head. The minimum value of the torque in the study area 50 N·m is observed at the point where the cutting angle of the soil is 45º, and the angular speed of rotation of the milling head is 4 rad/sec. The maximum torque 215 N·m was recorded at a cutting angle of 65º and a milling head speed of 10 rad/sec.Сonclusions. According to the results of the theoretical study of the process of cutting soil with the help of the milling working equipment of the excavator, the torque of the hydraulic motor necessary to rotate the milling head was established. The results of the theoretical studies carried out are recommended to be used to calculate the design and operating parameters in the design and creation of an experimental sample of milling working equipment.